2018
DOI: 10.7249/rr2088.1
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude and Sources of Disagreement Among Gun Policy Experts

Abstract: A A A An n n nd d d dr r r re e e ew w w w R R R R. . . . M M M Mo o o or r r rr r r ra a a al l l l, , , , T T T Te e e er r r rr r r ry y y y L L L L. . . . S S S Sc c c ch h h he e e el l l ll l l l, , , , M M M Ma a a ar r r rg g g ga a a ar r r re e e et t t t T T T Ta a a an n n nk k k ka a a ar r r rd d d d in AMERICA INI INI INI INI NITIA TIA TIA TIA TIATIV TIV TIV TIV TIVE C O R P O R A T I O N A P A P A P A P PART ART ART ART R OF OF OF OF F TH TH TH THE R E R E R E R RAND AND AND AND Gun Policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The estimated effect sizes are generally in line with what experts predicted for these types of marginal policy changes (2), which target firearm storage and use behaviors of only a narrow class of individuals or situations. While the IRRs are all descriptively close to 1, the magnitudes of the estimated effects are of a size considered important by policy makers and the public, with each of these policy levers potentially affecting more than 1,000 firearm deaths each year.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The estimated effect sizes are generally in line with what experts predicted for these types of marginal policy changes (2), which target firearm storage and use behaviors of only a narrow class of individuals or situations. While the IRRs are all descriptively close to 1, the magnitudes of the estimated effects are of a size considered important by policy makers and the public, with each of these policy levers potentially affecting more than 1,000 firearm deaths each year.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, one survey of 35 economists who study gun policy found that two-thirds believed that laws allowing the concealed carry of firearms would reduce murder rates (3), while a separate survey of gun policy experts found the opposite, with the majority believing that placing greater restrictions on concealed-carry permits would reduce gun deaths (4). A recent survey of firearm policy experts found that those who generally favor restrictive firearm regulations estimated that "stand-your-ground" (SYG) laws cause an 5% increase in homicides, while those who generally favored permissive regulations believed that these laws cause a 10% decrease in homicides (2). Similarly, experts favoring restrictive gun policies believed that child access prevention laws (CAP) would decrease firearm suicides by 5%, while experts favoring permissive regulations believed that such laws would have no effect on firearm suicides.…”
mentioning
confidence: 99%
“…Statistical power would obviously improve for all models if simulated with a larger effect size, and we believe that policymakers do and should care about gun laws that are on the order of increasing or decreasing the total number of firearm deaths by 1,000 per year. In our survey of a diverse sample of gun policy experts (Morral, Schell, and Tankard, 2018), we found that, when an expert believed a policy would increase suicide and homicide by 3 percent, the expert also believed the policy should not be implemented; when the expert believed the policy would decrease these outcomes by 3 percent, they strongly supported implementation. Similarly, other domains in which public policy could affect 1,000 deaths per year are often treated as serious problems or solutions.…”
Section: Concerns About Low Powermentioning
confidence: 92%
“…This effect size was also seen as large enough to be important within a RAND survey of gun policy experts drawn from both the gun control and gun rights communities (Morral, Schell, and Tankard, 2018). Specifically, we surveyed policy experts on their favorability toward 15 specific gun policies, as well as their beliefs about the expected effects of these policies.…”
Section: Law Effect Conditionsmentioning
confidence: 98%
“…Our research shows 6 Our criteria for studies that can provide scientific evidence of a causal effect of laws are explained in RAND that these are the kinds of questions for which there is strong disagreement between policy analysts and experts on opposing sides of gun policy debates. 9 One group believes that laws such as permitless carry, stand-your-ground, and the elimination of gun-free zones, will cause there to be fewer gun injuries, deaths, and mass shootings, and the other group believes that such laws will cause the opposite effects.…”
Section: Additional High-quality Research Is Needed To Craft Policiementioning
confidence: 99%